Phenological Water Balance Applications for Trend Analyses and Risk Management - Funk, Chris; Way-Henthorne, Juliet; Turner, Will (Frontiers in Climate, 2021)
The goal of this work is to develop and demonstrate methods that support effective agro-pastoral risk management in a changing climate. Disaster mitigation strategies, such as the Sendai Framework for Disaster Risk Reduction (SFDRR), emphasize the need to address underlying causes of disaster risk and to prevent the emergence of new risks. Such assessments can be difficult, because they require transforming changes in meteorological outcomes into sector-specific impact. While it is common to examine trends in seasonal precipitation and precipitation extremes, it is much less common to study how these trends interact with crop and pasture water needs. Here, we show that the Water Requirement (WR) component of the widely used WRSI can be used to enhance interpretations of precipitation changes. WR helps answer a key question: was the amount of rainfall received in a given season enough to satisfy a crop or pasture’s water needs? Our first results section focuses on analyzing spatial patterns of climate change. We show how WR values can be used to translate east African rainfall declines into estimates of crop and rangeland water deficits. We also show that increases in WR, during recent droughts, has intensified aridity in arid regions. In addition, using the PWB, we also show that precipitation increases in humid areas of western east Africa have been producing increasingly frequent excessive rainfall seasons. The second portion of our paper focuses on assessing temporal outcomes for a fixed location (Kenya) to support drought-management scenario development. Kenyan rainfall is decreasing and population is increasing. How can we translate this data into actionable information? The UN and WMO advise nations to proactively plan for agro-hydrologic shocks by setting aside sufficient grain and financial resources to help buffer low-crop production years. We show how precipitation, WR, crop statistics, and population data can be used to guide 1-in-10 and 1-in-25-year low crop yield scenarios, which could be used to guide Kenya’s drought management planning and development. The first and second research components share a common objective: using the PWB to translate rainfall data into more actionable information that can inform disaster risk management and development planning.